2014
DOI: 10.4236/ns.2014.612090
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteomics of the Extremophile Black Fungus <i>Cryomyces antarcticus</i> Using 2D-Electrophoresis

Abstract: The microcolonial black fungus Cryomyces antarcticus is an extremophile organism growing on and in rock in the Antarctic desert. Ecological plasticity and stress tolerance make it a perfect model organism for astrobiology. 2D-gel electrophoresis and MALDI-TOF/TOF mass spectrometry were performed to explore the protein repertoire, which allows the fungus to survive in the harsh environment. Only a limited number of proteins could be identified by using sequence homologies in public databases. Due to the rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…This is a recent, promising approach to investigate the presence of stress-associated genes and expressed products and their role in polyextremotolerance and oligotrophism in black yeasts. Recent studies have already provided significant evidence that black yeasts have a peculiar response to stress that differs considerably from those of common mesophilic hyphomycetes; this understanding is fundamental for understanding mechanisms that pushed these fascinating organisms to the deep freeze and the deep extremes in general Zakharova et al 2013Zakharova et al , 2014a. The study of Antarctic RIF is therefore well beyond a subject for just a few specialists; RIFs are becoming an everexpanding group for study, offering research opportunities in many basic fields as microbial ecophysiology, evolution and adaptation to extremes as well as to the recent and fascinating field of astrobiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a recent, promising approach to investigate the presence of stress-associated genes and expressed products and their role in polyextremotolerance and oligotrophism in black yeasts. Recent studies have already provided significant evidence that black yeasts have a peculiar response to stress that differs considerably from those of common mesophilic hyphomycetes; this understanding is fundamental for understanding mechanisms that pushed these fascinating organisms to the deep freeze and the deep extremes in general Zakharova et al 2013Zakharova et al , 2014a. The study of Antarctic RIF is therefore well beyond a subject for just a few specialists; RIFs are becoming an everexpanding group for study, offering research opportunities in many basic fields as microbial ecophysiology, evolution and adaptation to extremes as well as to the recent and fascinating field of astrobiology.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, protein protection may be mediated by the involvement of other protective factors such as sugars or fatty acids (Zakharova et al 2013). Indeed, recent 2D-gel electrophoresis and Maldi-TOF/TOF mass spectrometry demonstrated that the proteome of C. antarcticus deviates significantly from other fungi (Zakharova et al 2014a). (Onofri et al 2007a, b).…”
Section: Mechanisms Of Tolerance and Response To Stressesmentioning
confidence: 97%
“…In summary, the first analysis of the draft genome did not uncover any significant deviations of this genome from mesophilic hyphomycetes. Nevertheless, recent analysis of the proteome of this fungus under optimal suggest that the fungus has a special set of hitherto unknown proteins: A major part of the protein spots picked from 2 D-protein gel could not be identified based on mass spectrometry and data bank search [30] . Previous studies support the assumption that the fungus not only has a set of novel proteins but that these proteins are highly stress resistant because no change of the proteome pattern could be observed under stress conditions of draught or temperature; only an up-and down-regulation of a constant set of proteins was exhibited [8] , [30] .…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ]. MALDI-TOF is already widely used in fungal proteome research, such as that in yeast [ 24 ], A. fumigatus [ 25 ], and Cryomyces antarcticus [ 26 ]. Therefore, we applied the 2-DE technology and MALDI-TOF mass spectrometry in this project to investigate the plant pathogenic fungus S. sclerotiorum using proteomics analysis for identification of differentially expressed proteins during the compound appressorium formation ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics strategies, such as the two-dimensional gel electrophoresis (2-DE) approaches, have been confirmed as efficient, rapid, and powerful means to identify proteins (or genes) followed by mass spectrometry, and matrix-assisted laser desorption/ionization (MALDI) [ 21 ]. Large-scale analyses of proteins by 2-DE have been conducted in a number of organisms, such as animals [ 22 ], plants [ 23 ], yeast [ 24 ], and fungi [ 25 , 26 ], which contributes considerably to our understanding of gene functions in the postgenomic era. However, the development and application of such methods in the filamentous plant-pathogenic fungus S. sclerotiorum have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%